2014
DOI: 10.1098/rspb.2014.0539
|View full text |Cite
|
Sign up to set email alerts
|

Towards a synthesis of frameworks in nutritional ecology: interacting effects of protein, carbohydrate and phosphorus on field cricket fitness

Abstract: Phosphorus has been identified as an important determinant of nutritionrelated biological variation. The macronutrients protein (P) and carbohydrates (C), both alone and interactively, are known to affect animal performance. No study, however, has investigated the importance of phosphorus relative to dietary protein or carbohydrates, or the interactive effects of phosphorus with these macronutrients, on fitness-related traits in animals. We used a nutritional geometry framework to address this question in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
186
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(220 citation statements)
references
References 47 publications
(132 reference statements)
30
186
4
Order By: Relevance
“…However, diets with a P content of 0.1% and below or 1% and above could support maximal growth during 3 day time periods when animals had been fed on the optimal (0.5%) diets for most of their lives, suggesting insects have a considerable capacity to buffer effects of non-optimal P consumption. Long-term consumption of diets with a P content of 1.00% or higher suppressed growth, consistent with the 'intake target' behavior of S. americana and with observations of reduced performance of various aquatic consumers (Boersma and Elser, 2006) and some insect species when provided with diets well above the mean P levels for terrestrial leaves (Harrison et al, 2014;Loaiza et al, 2008;Smith, 1960). Together, these results demonstrate that ecologically relevant variation in plant P content affects the behavior and performance of this grasshopper.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…However, diets with a P content of 0.1% and below or 1% and above could support maximal growth during 3 day time periods when animals had been fed on the optimal (0.5%) diets for most of their lives, suggesting insects have a considerable capacity to buffer effects of non-optimal P consumption. Long-term consumption of diets with a P content of 1.00% or higher suppressed growth, consistent with the 'intake target' behavior of S. americana and with observations of reduced performance of various aquatic consumers (Boersma and Elser, 2006) and some insect species when provided with diets well above the mean P levels for terrestrial leaves (Harrison et al, 2014;Loaiza et al, 2008;Smith, 1960). Together, these results demonstrate that ecologically relevant variation in plant P content affects the behavior and performance of this grasshopper.…”
Section: Discussionsupporting
confidence: 79%
“…However, the development rate of the grasshopper Melanoplus bivittatus was unaffected by dietary %P of artificial diets, except for negative effects at the highest levels (Loaiza et al, 2008). Smith (1960) found similar results for M. bivittatus using fertilized wheat, as did Harrison et al (2014), who found no effects of dietary P intake on most fitness parameters of crickets (Gryllus veletis) except for some negative effects of high dietary P on male chirping rate. Finally, fertilization of plots with phosphate increased survival, body size and development rate of one planthopper species but not another (Huberty and Denno, 2006).…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Thus, C. cosyra females opted for a protein and carbohydrate intake promoting strong egg production per day, rather than across their entire lives. The effects of protein and carbohydrate intake on lifespan in our study species were similar to those observed in other studies applying the GF to Tephritidae (Fanson & Taylor, 2012; Fanson et al., 2009), Diptera (Jensen et al., 2015; Lee et al., 2008), and other herbivorous insect orders (Harrison, Raubenheimer, Simpson, Godin, & Bertram, 2014; Maklakov et al., 2008). As in these other studies, we found that lifespan was optimized when flies consumed high quantities of a carbohydrate‐biased diet.…”
Section: Discussionmentioning
confidence: 99%